2018
DOI: 10.3390/s18030817
|View full text |Cite
|
Sign up to set email alerts
|

Cyber and Physical Security Vulnerability Assessment for IoT-Based Smart Homes

Abstract: The Internet of Things (IoT) is an emerging paradigm focusing on the connection of devices, objects, or “things” to each other, to the Internet, and to users. IoT technology is anticipated to become an essential requirement in the development of smart homes, as it offers convenience and efficiency to home residents so that they can achieve better quality of life. Application of the IoT model to smart homes, by connecting objects to the Internet, poses new security and privacy challenges in terms of the confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
141
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(153 citation statements)
references
References 53 publications
0
141
0
Order By: Relevance
“…It is hoped that this will allow for a more secure and private system, although this remains for further exploration. However, as researchers continue to consider the approaches combined in this work, like [28] for Privacy-by-Design in IoT, and [3] for IoT security with OCTAVE-Allegro, it is expected that this merger will aid developers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hoped that this will allow for a more secure and private system, although this remains for further exploration. However, as researchers continue to consider the approaches combined in this work, like [28] for Privacy-by-Design in IoT, and [3] for IoT security with OCTAVE-Allegro, it is expected that this merger will aid developers.…”
Section: Discussionmentioning
confidence: 99%
“…This more recent refinement is targeted toward much smaller groups and individuals aiming to develop "broad assessment of an organization's operational risk environment...without the need for extensive risk assessment knowledge" [9]. This approach has recently begun to be investigated in the IoT domain toward gaining an understanding of IoT security, as in [3]. The OCTAVE-Allegro methodology consists of eight steps toward four key tasks, namely establishing drivers, profile assets, identification of threats, and identification and mitigation of risks, [9].…”
Section: Octave-allegro Methodology For Corementioning
confidence: 99%
“…A comprehensive study on the security of an IoT based smart home has been presented in [20], where the authors have identified various security risks from both internal and external sources. This work mainly focused on identification of risks and their impact pertaining to the smart home application.…”
Section: Security In Iotmentioning
confidence: 99%
“…Confidentiality, integrity, and availability are three important security concepts of applications and services in IoT-based smart environments; thus, to address these concerns, information security in IoT systems requires greater research focus [2]. For example, IoT-based smart homes face security and privacy challenges that span all layers of the IoT architecture [31].…”
Section: Security Challenges In Iot-based Smart Environmentsmentioning
confidence: 99%